Pengelolaan Lorong Wisata Berbasis Teknologi Internet of Things (IoT) di Kota Makassar - Wahyudi; Hartini Ramli; Moch. Kay Muddin Asnur; Wulan Purnamasari (Fakultas Teknik, Universitas PGRI Banyuwangi, 2024)
The management of lorong wisata as one of the local tourist destinations in Makassar City requires an innovative approach to improve service quality and attractiveness for tourists. Internet of Things (IoT) technology offers an effective solution to integrate a more efficient and modern management system. This service programme aims to implement IoT-based management of tourist corridors, including real-time monitoring of cleanliness, security, and management of public facilities. The method used involves training for local communities in the utilisation of IoT technology and the installation of IoT devices in tourist alleys. The results of the service showed an increase in efficiency in the management of tourist passages, as well as more active community involvement in maintaining and utilising existing facilities. The use of IoT technology is proven to be able to accelerate responses to environmental and operational problems, thereby improving the quality of the tourist experience. In the future, it is hoped that this IoT-based management model can be replicated in other areas to support sustainable tourism development.